The influence of entrepreneurial failure education on intention to reengage in entrepreneurship among university students: mediation of entrepreneurial resilience and moderating model of regulatory focus - Ma, Lihua; Wang, Yupu; Wang, Jichao; Chen, Yufei; Yan, Huizhe (Frontiers in Education, 2025)
Entrepreneurial Failure Education (EFE) is a critical approach for college students to develop capabilities in addressing entrepreneurial challenges; however, while prior research has focused on the impact of entrepreneurship education on initial entrepreneurial intention, the influence of EFE on Intention to Reengage in Entrepreneurship (IRE) remains underexplored, with gaps in understanding its underlying mechanism and boundary conditions, this study aimed to address three core questions: (1) the direct effect of EFE on college students' IRE; (2) the mediating role of Entrepreneurial Resilience (ER) in the EFE-IRE relationship; (3) the moderating role of regulatory focus (promotion vs. prevention focus) in the EFE-IRE relationship. This study adopted a two-wave questionnaire survey design, targeting Chinese college students with prior entrepreneurial failure experience; a total of 700 questionnaires were initially distributed, with 583 valid responses finally collected, and mature validated scales were used to assess EFE, ER, regulatory focus (promotion focus and prevention focus), and IRE, while stepwise regression, exploratory factor analysis (EFA), reliability and validity tests, and the Bootstrap method were applied to verify the mediating and moderating effects. The results showed that: (1) EFE exerted a significant positive impact on college students' IRE; (2) ER played a partial mediating role in the EFE-IRE relationship-EFE significantly enhanced ER, which in turn positively promoted IRE, and the direct effect of EFE on IRE remained significant but weakened after controlling for ER; (3) regulatory focus moderated the EFE-IRE relationship: promotion focus positively strengthened this association, while prevention focus negatively weakened it. Theoretically, this study integrates perspectives from entrepreneurship, pedagogy, and psychology to clarify the formation mechanism and practical pathways of college students' IRE, filling gaps in existing research on EFE's impact on post-failure entrepreneurial reengagement; practically, the findings provide actionable insights for university entrepreneurship education reform, urging a shift from the traditional “success-oriented” model to a comprehensive EFE system to foster students' ER, and also offer evidence-based support for enhancing students' post-failure IRE and promoting their sustainable entrepreneurship.